Diseases of field crops diagnosis and management. Volume 2, Pulses, oil seeds, narcotics, and sugar crops - Srivastava, J. N. (Plant pathologist); Singh, A. K. (Ajay Jumar) (Agronomist) (Palm Bay, Fla. : Apple Academic Press, 2020)
Plant diseases cause yield loss in crop production, poor quality of produce, and great economic losses as well. Knowledge of the perpetuation and spread of the pathogens and various factors affecting disease development is an important need. Disease diagnosis is the prime requirement for determining preventive or curative measures for effective disease management. This new 2-volume set, Diseases of Field Crops, helps to fill the need for research on plant diseases, their effects, how they spread, and effective management measures to mitigate their harmful consequences. The volumes in this set showcase recent advances in molecular plant pathology and discuss appropriate diagnostic techniques for identification of causal agents and diseases, providing the information necessary to establish management strategies. The chapters in these two volumes include detailed description of symptoms, causal organisms, disease cycles, epidemiology, and management techniques of economically important diseases. The volumes explore existing strategies and offer new methods that can be used in an integrated manner and with a comprehensive approach for the management of major diseases of the field crops. Also taken into consideration is the impact of global climate change on the spread and severity of plant diseases. This volume covers pulses, oil seeds, narcotics, and sugar crops. Each of the chapters focuses on one crop, with a detailed account of symptoms, causal organisms, disease cycles, epidemiology, and management of the diseases caused by fungi, bacteria and viruses. Some crops discussed include green gram, chickpeas and peas, lentils, soybeans, groundnuts, sunflowers, sugarcane, tobacco, and others. Volume 1 focuses on cereals, small millets, and fiber crops.
Volume 2: Pulses, Oil Seeds, Narcotics, and Sugar Crops1. Current Status of Bengal Gram Diseases and Their Management StrategiesK. K. Sharma and Ashish Kumar2. Current Status of Chickpea Diseases and Their Integrated ManagementDurga Prasad Awasthi and Ranganathswamy Math3. Important Diseases of Field Pea (Pisum sativum Var. Arvense) and Their ManagementA. Khulbe and K. K. Sharma4. Important Diseases of Green Gram (Vigna radiata L. Wilczek) and Their ManagementJai Singh, K. K. Mishra, and A. K. Chaubey5. Integrated Disease Management of Horse Gram (Macrotyloma uniflorum)Upma Dutta, Sachin Gupta, Anamika Jamwal, and Sonika Jamwal6. Diseases of Lentil (Lens esculentus Moench) and Their ManagementRanganathswamy Math, A. K. Patibanda, and J. N. Srivastava7. Diseases of Pigeon Pea (Cajanus cajan L. Millsp.) and Their ManagementManoj Kumar Kalita8. Integrated Disease Management in PigeonpeaSanjeev Kumar et al.9. Important Diseases of Soybean Crop and Their ManagementV. K. Yadav et al.10. Current Status of Castor Diseases and Their ManagementN. M. Gohel, B. K. Prajapati, and Harshil V. Parmar11. Current Status Groundnut (Arachis hypogae L.) Diseases and Their ManagementKottramma C. Addangadi and Ranganathswamy Math12. Current Status of Linseed (Linum usitatisimum L.) Diseases and Their ManagementRanganathswamy Math and Durga Prasad Awasthi13. Present Scenario of Rapeseed-Mustard Diseases and Their Integrated ManagementP. D. Meena and Ashish Sheera14. Important Diseases of Sesamum (Sesamum indicum L.) and Their ManagementV. B. Singh et al.15. Sunflower Diseases and Their Management by Integrated ApproachKothakota Venkataramanamma, Lingan Rajendran, and C. Gopalakrishnan16. Diseases of Taramira (Eruca sativa Mill.) and Their Management: An Indian PerspectiveK. K. Sharma and J. N. Srivastava17. Current Status of Smut Disease of Sugarcane and Its Management in IndiaGeeta Sharma and Jai Singh18. Diseases of Tobacco (Nicotiana tabacum Linn.) and Their ManagementK. Jayalakshmi, H. Ravindra, and J. Raju
OCLC-licensed vendor bibliographic record.
Keywords: Plant diseases -- Molecular aspects; Phytopathogenic microorganisms -- Control